Eksplorasi Peta Jalan Penelitian Skripsi Program Studi Pengembangan Masyarakat Islam UIN Sunan Ampel Surabaya: Sebuah Analisis Kualitatif dalam Perspektif Integrasi Twin Towers: Sebuah Analisis Kualitatif dalam Perspektif Integrasi Twin Towers - Fitriyah, Ries Dyah; Falasifah, Nihlatul; Arida, Vera (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The twin towers paradigm in the Islamic Community Development Study Program at UIN Sunan Ampel Surabaya emphasizes Islamic integration and community empowerment. This research designs a road map that suits the paradigm and needs of the community, so that the results meet academic standards while directly benefiting the community as empowerment partners. The method used in this research uses a qualitative approach through the results of FGD (Focus Group Discussion) and interviews. The research results show that there are strategic issues being developed in line with the strategic issues of UIN Sunan Ampel Surabaya, such as basic scientific research for scientific development in the Islamic Community Development Study Program to strengthen study program competencies, community-based research (community engagement research) in the field of community service with various community-based research approaches and methods such as Participatory Action Research (PAR) and Asset Based Community Development (ABCD), environmental issues including the themes of environmental conservation, natural disasters and eco-tourism using an Islamic perspective.